Mu opioid receptor signaling in the nucleus accumbens shell increases responsiveness of satiety‐modulated lateral hypothalamus neurons. (4th May 2017) - Tandon, Shashank; Keefe, Kristen A.; Taha, Sharif A.
Abstract: Opioid signaling in the nucleus accumbens shell (sNAcc) has been implicated in hedonic feeding and binge eating behavior. The sNAcc projects to the lateral hypothalamus (LH), and this pathway has been suggested to modulate palatability‐driven feeding behavior. In this study, we investigated the effects of sNAcc mu opioid receptor (MOR) stimulation on firing rates of LH neurons in previously sated rats. Neural firing in the LH was recorded while food‐deprived rats performed an operant task to obtain sweetened Intralipid (a 4% fat emulsion containing 5% sucrose) before and after bilateral sNAcc infusion of either a MOR agonist [D‐Ala2, N‐MePhe4, Gly‐ol]‐enkephalin (DAMGO) or a saline control solution. During sessions in which saline was infused into the sNAcc, the number of trials completed after infusion were significantly lower than the number completed before infusion, likely reflecting animals' increased satiety state. During sessions in which DAMGO was infused into the sNAcc, the decrease in the number of trials completed (comparing post‐ vs. pre‐infusion trials) was significantly attenuated. Electrophysiological recording showed that the percentage of LH neurons showing an excitatory response due to behavioral events (cue presentation, lever press, lever retraction, and consumption) was reduced in post vs. pre‐saline infusion period. However, the percentage of LH neurons showing excitatory responses to the same behavioral events was similar in pre‐ and post‐DAMGO infusion periods. These findings suggest that MOR stimulation in sNAcc leads to an increase in stimulus‐evoked excitatory signaling in LH neurons which could contribute to preventing satiety‐induced decline in palatable food intake. Abstract : Mu opioid receptor agonist (DAMGO) infusion in nucleus accumbens shell (sNAcc) attenuates satiety in an operant task to obtain sweetened Intralipid. Satiety is associated with decrease in percentages of responsive lateral hypothalamus (LH) neurons, especially those showing excitation, to behavioral events in the task. DAMGO infusion in sNAcc attenuates the decrease in responsiveness. This increased stimulus‐evoked signaling in LH neurons may contribute to persistence of feeding behavior.